2017
DOI: 10.1007/s10295-016-1880-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of rapamycin production by metabolic engineering in Streptomyces hygroscopicus based on genome-scale metabolic model

Abstract: Rapamycin, as a macrocyclic polyketide with immunosuppressive, antifungal, and anti-tumor activity produced by Streptomyces hygroscopicus, is receiving considerable attention for its significant contribution in medical field. However, the production capacity of the wild strain is very low. Hereby, a computational guided engineering approach was proposed to improve the capability of rapamycin production. First, a genome-scale metabolic model of Streptomyces hygroscopicus ATCC 29253 was constructed based on its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…In another study, based on a genome-scale metabolic model, pfk (encoding 6-phosphofructokinase) was deleted, and two target genes including dahp (encoding a DAHP synthase) and rapK (encoding a chorismatase) were overexpressed, resulting in approximately 30.8%, 36.2% and 44.8% increases in rapamycin titers, respectively. Combinatorial metabolic engineering by pfk knockout and co-overexpression of dahP and rapK , led to further enhanced rapamycin production by 142.3%, achieving a 250.8 mg/l rapamycin titer ( 49 ). Thus, compared to previous studies utilizing static metabolic engineering approaches, our EQCi-based regulation of multiple essential pathways is much more effective for improving rapamycin titers.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, based on a genome-scale metabolic model, pfk (encoding 6-phosphofructokinase) was deleted, and two target genes including dahp (encoding a DAHP synthase) and rapK (encoding a chorismatase) were overexpressed, resulting in approximately 30.8%, 36.2% and 44.8% increases in rapamycin titers, respectively. Combinatorial metabolic engineering by pfk knockout and co-overexpression of dahP and rapK , led to further enhanced rapamycin production by 142.3%, achieving a 250.8 mg/l rapamycin titer ( 49 ). Thus, compared to previous studies utilizing static metabolic engineering approaches, our EQCi-based regulation of multiple essential pathways is much more effective for improving rapamycin titers.…”
Section: Discussionmentioning
confidence: 99%
“…Avermectin production is correlated with increased activity of pentose phosphate pathway in S. avermetilis [ 48 ]. S. hygroscopicus Δ pfk mutant increases rapamycin production by 30.8% [ 21 ]. Here we showed that S. albus Δ pfk strain is more resistant to diamide than the wild type.…”
Section: Discussionmentioning
confidence: 99%
“…Sco4 includes biosynthetic pathways of eleven secondary metabolites, but it is still far from fully covering the information on 27 BGCs predicted using a genome mining tool antiSMASH (Table ). Such dearth of information on secondary metabolism is observed even more in GEMs of other actinomycetes, most of which cover biosynthetic pathway of only one target antibiotics, for example rapamycin in Streptomyces hygroscopicus , tacrolimus (FK506) in S. tsukubaensis , spinosad in Saccharopolyspora spinosa and balhimycin in Amycolatopsis balhimycina . In this regard, computational resources dedicated to studies on secondary metabolites should additionally be considered to more comprehensively describe secondary metabolism in the GEMs of actinomycetes, including genome mining tools for the BGC detection, cheminformatic tools for compound identification and dereplication, and databases for BGCs and secondary metabolites .…”
Section: Status Of Genome‐scale Metabolic Reconstruction Of Actinomycmentioning
confidence: 99%